2009
DOI: 10.1088/0004-637x/701/2/l95
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence for Young Radio Galaxies Is Triggered by Accretion Disk Instability

Abstract: Bolometric luminosities and black hole (BH) masses are estimated by various methods for a sample of young radio galaxies with known ages. We find that the ages are positively correlated with the bolometric luminosities in these young radio galaxies. This positive correlation is consistent with the theoretical prediction based on the radiation pressure instability of accretion disks in Czerny et al. The ages of young radio galaxies are also found to be consistent with the theoretical durations of outbursts in B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
5
31
0
Order By: Relevance
“…Therefore the poloidal component of the magnetic field accelerates the particles, and at the same time it forms the relativistic jet and surrounding wind. The accretion disk of NLS1s is luminous enough to be in the radiation pressure dominated regime in which radiative instability occurs (Moderski & Sikora 1996;Ghosh & Abramowicz 1997;Czerny et al 2009;Wu 2009;Foschini 2011a). This instability might translate into a change in angle, and then in an intermittent BP contribution to the jet.…”
Section: Radio Quiet Versus Radio Loudmentioning
confidence: 99%
“…Therefore the poloidal component of the magnetic field accelerates the particles, and at the same time it forms the relativistic jet and surrounding wind. The accretion disk of NLS1s is luminous enough to be in the radiation pressure dominated regime in which radiative instability occurs (Moderski & Sikora 1996;Ghosh & Abramowicz 1997;Czerny et al 2009;Wu 2009;Foschini 2011a). This instability might translate into a change in angle, and then in an intermittent BP contribution to the jet.…”
Section: Radio Quiet Versus Radio Loudmentioning
confidence: 99%
“…However, Altamirano et al (2011) recently reported another source, IGR J17091-3624, that seems to show variability similar to that of GRS 1915+105 at lower luminosity, which suggests that there may be other variables associated with limit-cycle behavior in X-ray binaries. Although the analogous limit cycle in active galactic nuclei (AGNs) is difficult to observe directly due to its long timescale, some intermittent activity in young radio galaxies has been ascribed to thermal instability in the disk (Czerny et al 2009;Wu 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A consistent number of restarting radio sources have been found in the past 20 yr, and hypotheses about their nature have been proposed (Czerny et al 2009;Wu 2009;Marecki et al 2006). Some of them correspond to GPS sources or CSS sources, which are known to be young radio sources.…”
Section: Low-frequency Componentsmentioning
confidence: 98%